Topological defect and sp3/sp2 carbon interface derived from ZIF-8 with linker vacancies for oxygen reduction reaction. (25th January 2023) - Gao, Haixing; Wang, Shuo; Cheong, Weng-Chon (Max); Wang, Kaixi; Xu, Huifang; Huang, Aijian; Ma, Junguo; Li, Jiazhan; Ip, Weng-Fai (Andy); San Hui, Kwan; Dinh, Duc Anh; Fan, Xi; et al.
Abstract: Defects in nanocarbon materials can trigger their intriguing electrochemical properties and potential applications, but their synthesis is challenging. Herein, we report the synthesis of ultrathin nitrogen-doped carbon nanosheets with intrinsic defects through the pyrolysis of ZIF-8 with linker vacancies. The as-synthesized electrocatalyst exhibits excellent oxygen reduction reaction (ORR) activity with an onset potential and half-wave potential of 1.05 and 0.873 V vs. RHE, respectively, outperforming the reported metal-free ORR electrocatalysts. It also shows a commercial Pt/C-comparable performance in zinc–air battery with a power density of 154.4 mW cm −2 . Characterization and DFT calculation results suggest the adjacent sp 3 -carbon in carbon pentagon can significantly strengthen the adsorption and activation of oxygen molecules on sp 2 -carbon, hence the potential determining step is altered and ORR overpotential is lowered. This work highlights a promising green synthesis strategy of MOF-derived metal-free nanocarbon materials for wide application in advanced energy technologies. Graphical abstract: Image 1 Highlights: Hydrothemal synthesis of ZIF-8 with linker vacancies by addition of boric acid. Rich edge sites, carbon pentagon and sp 3 hybrization in derived metal-free carbon. Superior ORR and zinc–air battery performance among reported metal-free materials. Synergistic effect of topological defect and hybrization state.